PIRMESHKI SETTLEMENT AND ITS NECROPOLIS - Gadziev, Murtazali Serazutdinovic (History, Archeology and Ethnography of the Caucasus, 2018)
The article is devoted to results of visual inspections on the settlement Pirmeshki, the first settlement in the system of the 42-km defensive line of the Mountain wall (Dagh bary), situated near the citadel of Derbent (600 m SW). The author gives the detailed description of the settlement, provides historical and cartographical data on the settlement, carries out the analysis of the toponym Pirmeshki (*Pir-Dimishki). In the territory of the settlement there are two fortifications of the Mountain wall (forts 4 and 5) built in the end of the 560-s - the beginning of the 570-s as a component of the Derbent defensive complex. Judging by the situation, the settlement played an important strategic role in the system of defense of the initial part of the Mountain wall and the whole Derbent complex: it together with forts 4 and 5 and next forts 1-3 prevented possibility of going round Derbent right to the west from the Naryn-Kala citadel. The article gives a short review of the necropolis of the settlement Pirmeshki on which 77 sarcophagus-shaped funerary monuments (from 0,9 m up to 2,6 m long) dated by the second half of the 11th - 12th centuries were revealed. The author provides data about such funerary monuments in the territory of Daghestan (over 30 sites) and allocates three zones of their concentration: 1) Derbent and its historical district, including the Mountain wall and part of Tabasaran; 2) Caytagh (medieval Khaydak); 3) Southern Daghestan (medieval Lakz). The author considers the places of concentration of the monuments as the locations of Seljuk garrisons and basic territories in military and religious expansion of the Seljuks in the Northeast Caucasus